Ensiklopedia Malaysiana (Kuala Lumpur Anzagain, 1996)
Encyclopedia of Malaysia.
jil. 1. A-Arang batu -- jil. 2. Aras dasar-Bintang Timur -- jil. 3. Bintik-Czech -- jil. 4. D-Futurisme -- jil. 5. G-Hythergraph -- jil. 6. I-Kelikatan -- jil. 7. Kelikir-Leucopholis -- jil. 8. Leukemia-Myrtales -- jil. 9. N-Pencetak -- jil. 10. Penci lan-Psikologi -- jil. 11. Psikoneurosis-Sikat sesunggut -- jil. 12. Sikh-Tembok -- jil. 13. Tembok Berlin-Zygnematales -- jil. 14. Kamus (A-K)--jil. 15. Kamus (L-Z)--jil. 16. Peribahasa & sinonim -- jil. 17. Indeks.
Includes bibliographical references and indexes
jil.1 : A-Arang batu, jil.2 : Aras dasar-Bintang Timur, jil.3 : Bintik-Czech, jil.4 : D-Futurisme, jil.5 : G-Hythergraph, jil.6 : I-Kelikatan, jil.7 : Kelikir-Leucopholis, jil.8 : Leukemia-Myrtales, jil.9 : N-Pencetak, jil.10 : Pencilan-Psikologi, ji l.11 : Psikoneurosis-Sikat sesunggut, jil.12 : Sikh-Tembok, jil.13 : Tembok Berlin-Zygnematales, jil.14 : Kamus (A-K), jil.15 : Kamus (L-Z), jil.16 : Peribahasa & sinonim, jil.17 : Indeks
Includes bibliographical references (v. 16, p. [367]-383) and index.
Keywords: Encyclopedias and dictionaries, Malay -- Malaysia; Malaysia -- Encyclopedias; Encyclopedias and dictionaries, Malay -- Malaysia; Encyclopedias and dictionaries,Malay -- Malaysia; Malaysia -- Encyclopedias; Malaysia -- Encyclopedias